Adjuvant chemotherapy for perihilar cholangiocarcinoma: A population-based comparative cohort study. Issue 6 (June 2022) - Kamarajah, Sivesh K.; Al-Rawashdeh, Wasfi; Parente, Alessandro; Atherton, Phil; Salti, George I.; Dahdaleh, Fadi S.; Manas, Derek; Hilal, Mohammed Abu; White, Steven A.
Abstract: Background: Data supporting routine use of adjuvant chemotherapy (AC) compared to no AC (noAC) for perihilar cholangiocarcinoma (hCCA) is unclear. This study aimed to determine whether AC improves long-term survival following resection for hCCA. Methods: Patients receiving resection for hCCA followed by AC or no AC from 2010 to 2016 were identified from the National Cancer Database (NCDB). Propensity score matching (PSM) and Cox regression was performed to account for selection bias and analyze impact of AC on overall survival. Results: Of 924 (56%) noAC and 719 (44%) AC, 320 noAC and 320 AC patients remained after PSM. After matching, AC was associated with improved survival (median: 28.2 vs 19.9 months, p < 0.001), which remained after multivariable adjustment (HR: 0.61, CI95% : 0.50–0.75, p < 0.001). On multivariable interaction analyses, the benefit of AC over no AC persisted irrespective of nodal status: N0 (HR: 0.62, CI95% : 0.41–0.92, p = 0.019), N1 (HR: 0.52, CI95% : 0.36–0.75, p = 0.001), N2 (HR: 0.31, CI95% : 0.11–0.90, p = 0.032), Nx (HR: 0.22, CI95% : 0.09–0.55, p = 0.001) and margin status: R0 (HR: 0.74, CI95% : 0.57–0.97, p = 0.026), R1 (HR: 0.31, CI95% : 0.21–0.47, p < 0.001). Stratified analysis by nodal, margin and AC status demonstrated consistent results. Conclusion: AC following resection for hCCA was associated with improved survival in this study, even in margin-negative and node-negative disease. These findings suggest incorporation of AC into multimodality therapy for hCCA in all cases, where appropriate.